The use of cetirizine in allergic contact dermatitis patients at Sekip Palembang Health Center - Rukmana, Cici Chintya Aulia; Harahap, Debby Handayati; Theodorus (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2025)
World Allergy Organization (WAO) reported that 22% of the global population experiences allergies, and this prevalence continues to increase each year. The prevalence of dermatitis in Indonesia is quite high, at 6.78%, with the highest rate in South Kalimantan (11.3%) and the lowest in West Sulawesi (2.57%). In South Sumatra, approximately 2,584,000 people suffer from dermatitis. Therapy for allergic contact dermatitis patients includes medicamentous treatments, such as systemic antihistamines, with cetirizine being one of the options. This study aimed to determine the pattern of cetirizine use, including the frequency, duration of administration, and the characteristics of allergic contact dermatitis patients such as gender and age who received cetirizine therapy. The drug utilization study of cetirizine was conducted in December 2021 at the Sekip Palembang Community Health Center, involving 34 out of 49 patients who met the inclusion criteria. The sampling method used was total sampling. The majority of allergic contact dermatitis patients were late elderly individuals, aged 56-65 yr (32.4%), and women (58.8%). Rationality assessment showed good results in terms of diagnosis (100%), indication (100%), duration of drug administration (97.1%), frequency of drug administration (100%), and drug interactions (93.7%). This study hopefully can enhance the effectiveness of cetirizine usage, enabling healthcare providers to prescribe the medication more rationally according to the patients' allergic symptoms.